What if Hitler had won WWII and met Kennedy in 1964? Perception and evaluation of counterfactual historical fiction - Kakimova, Ainur; Salgaro, Massimo (Frontiers in Human Neuroscience, 2024)
The paper provides empirical evidence on the cognitive processing and the perception of counterfactual historical fiction and its effects on readers' fascism receptivity, superstitious beliefs, and satisfaction with current political situation, i.e., the present state of politics. The genre of counterfactual historical fiction depicts alternative realities in which history follows a different path with regard to the official version of historiography. For example, Robert Harris (1992) in his novel Fatherland depicts the counterfactual world in which Hitler won WWII. It was hypothesized that reading such genre is associated with additional cognitive costs. It was also assumed that the genre might be perceived with less perceived realism and more aesthetic feeling than historical fiction. To test these hypotheses, we gave two groups of readers to read two versions of some paragraphs of Fatherland: one group read the text in the original version in which a counterfactual reality is described in which Hitler is still alive in 1964. The other group read a manipulated version in which the events described are made plausible because they are backdated to 1941. Based on the literature, it was expected that reading literary text changes readers' views on their political situation and life condition. The study triangulated methods using both online eye tracking method and self-report questionnaires to obtain comprehensive data. The results suggest that counterfactual historical fiction is associated with cognitive demands for the first point of divergence (the first linguistic cue in the text that shows counterfactuality), by inducing less perceived realism of history (factuality), and more surprise. Although, both texts have impact on readers: less agreement with fascism, decrease in superstitious beliefs and increase in political evaluation after reading.